Evolução dos cartazes de cinema de ficção científica: uma linha do tempo sob a perspectiva do design gráfico - Castilho, Ana Cristina Lemes (Universidade do Vale do Rio dos Sinos, 2013)
Throughout history, an important intersection between the development of the modern poster, graphic design and the cinema is found. Along with that intersection, is the popularization of the genre of science fiction. This paper takes advantage of the intersection between these expressions and will try to answer how the evolution of science fiction movie posters took place, from the perspective of graphic design, since the birth of the genre to the present day. To do so, the following specific objectives were defined: to understand the evolution of the film poster as a media for the cinema; to establish a link between graphic design and the social context of the posters; and to draw a timeline with the posters. To achieve the proposed objectives, this study will be divided into four stages. The first stage will be a bibliographical study on relevant topics. The second step will be the identification and definition of science fiction movie posters that will enable the analysis. The third step will be the analysis of the posters based on the previous bibliographical study, and finally, the fourth stage, will be to draw a timeline based on the selected posters.
Keywords: Design gráfico; Cartaz; Cinema; Ficção científica; Graphic design; Poster; Cinema; Science fiction